2021
DOI: 10.18632/aging.203090
|View full text |Cite
|
Sign up to set email alerts
|

Cistanche deserticola polysaccharides alleviate cognitive decline in aging model mice by restoring the gut microbiota-brain axis

Abstract: Recent evidence suggests alterations in the gut microbiota-brain axis may drive cognitive impairment with aging. In the present study, we observed that prolonged administration of D-galactose to mice induced cognitive decline, gut microbial dysbiosis, peripheral inflammation, and oxidative stress. In this model of agerelated cognitive decline, Cistanche deserticola polysaccharides (CDPS) improved cognitive function in Dgalactose-treated mice by restoring gut microbial homeostasis, thereby reducing oxidative st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…The potential active components of ZSWF regulating intestinal flora of DCI mice may be polysaccharides in Cistanches Herba and alkaloids in Phellodendri Chinensis Cortex. Previous studies confirmed that Cistanche polysaccharides demonstrate a clear regulatory effect on intestinal flora (Fu et al, 2020;Fan et al, 2021;Gao et al, 2021). Although accumulative studies confirmed that berberine, the main alkaloid component of Phellodendri Chinensis Cortex, can protect cognitive function (Aski et al, 2018;Shinjyo et al, 2020;Yi et al, 2021), subsequent studies gradually recognized that regulating intestinal flora may be the initial link of berberine improving cognitive function (Zhang et al, 2020b;Habtemariam, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…The potential active components of ZSWF regulating intestinal flora of DCI mice may be polysaccharides in Cistanches Herba and alkaloids in Phellodendri Chinensis Cortex. Previous studies confirmed that Cistanche polysaccharides demonstrate a clear regulatory effect on intestinal flora (Fu et al, 2020;Fan et al, 2021;Gao et al, 2021). Although accumulative studies confirmed that berberine, the main alkaloid component of Phellodendri Chinensis Cortex, can protect cognitive function (Aski et al, 2018;Shinjyo et al, 2020;Yi et al, 2021), subsequent studies gradually recognized that regulating intestinal flora may be the initial link of berberine improving cognitive function (Zhang et al, 2020b;Habtemariam, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, natural polysaccharides also suppress excessive inflammatory responses by improving the intestinal microbiota composition, promoting SCFAs production, strengthening intestinal barrier function and reducing pro-inflammatory mediators ( Tang et al, 2019 ). A plant polysaccharide from Cistanche deserticola improves cognitive function in mice in a D -galactose induced aging model by restoring homeostasis of the gut-microbiota-brain axis ( Gao et al, 2021 ). Therefore, polysaccharides may mediate intestinal flora and related metabolites against NDs.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal microbiota participates in the processes of both health regulation and disease progression. 8,9 An imbalance of intestinal microbiota is one of the major causes of constipation. 47 In this study, we found that gut microbiota had changed greatly in the aged constipated rats, including reduction of intestinal bacterial diversity at the class, order, and genus levels, as well as the abnormalities of 9 gut microbiota.…”
Section: Papermentioning
confidence: 99%
“…6 Among them, polysaccharides are a principal component which not only exhibit effects on constipation 7 but also improve the symptoms of aging. 8 However, the research of mechanisms of Cistanche deserticola polysaccharides (CDPS) on constipation merely scratches the surface, requiring new technologies and strategies deeply.…”
Section: Introductionmentioning
confidence: 99%